Diseño de equipo de gateo para bebés con PCI y/o retraso de desarrollo psicomotor (2020)
Crawling gives a child a sense of spatial location, coordination, and muscle strengthening. This last aspect becomes a fundamental characteristic for the treatment of pathologies that slow down the normal development of a baby, such as delayed psychomotor development (PMD) and / or infantile cerebral palsy (PCI). Normally, crawling occurs between 6 and 11 months of age, but under special conditions, it can occur as early as 8 months or much later. This project aims to design a crawling experience for babies with the mentioned pathologies. This experience is expected to unfold in the context of infant physical therapy for babies between 6 and 36 months. A learning environment must be created for the child, ensuring that each element works in favor of three main actors: physiotherapist, father and baby.